A hybrid vanadium redox/lithium-ion energy storage system for off-grid renewable power - Gan, L; Howey, D (Institute of Electrical and Electronics Engineers, 2017)
In off-grid renewable power systems, batteries are often used to balance the mismatch between load and electricity generation. The mismatch may be more severe in small-scale systems due to the lack of averaging effect seen in larger power systems. In the former, batteries have to cope with rapid power fluctuations whilst still delivering power to consumers. A vanadium redox flow battery (VRB) may seem to be an ideal energy storage system in this case due to its well-known durability and ease of expanding its energy capacity. However, the associated parasitic losses used for electrolyte circulation will dominate when the charge/discharge power is low, and this is particularly inefficient when no other means of energy storage is available. This work proposes the hybridisation of VRB and lithium-ion batteries (LIBs), which complement one another in terms of energy capacity, power handling capability and durability. The trade-off between the parasitic losses of VRB vs. the degradation of LIB presents an interesting optimisation problem. To investigate this, a VRB system which consists of a stack model and a mechanical model was developed before establishing an appropriate energy management system (EMS) using a conventional rule-based approach. In addition, a mixed integer linear programming technique was used to solve the multi-objective optimisation problem in order to investigate the operation of the proposed hybrid energy storage system (HESS) using realistic solar irradiance and load demand profiles. A sensitivity analysis was conducted with different weights for the two objectives. A high-fidelity physical model (Matlab/Simulink) was used to study the underlying transients and to validate the control strategies.